2013
DOI: 10.2169/internalmedicine.52.9340
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Response Induced by 21-day Sorafenib Therapy in a Patient with Advanced Hepatocellular Carcinoma

Abstract: The response rate and overall survival after sorafenib administration in patients with advanced hepatocellular carcinoma are unsatisfactory. We herein present the case of a 65-year-old man with multiple lung metastases of hepatocellular carcinoma. Because the patient had liver cirrhosis of Child-Pugh B accompanied by pancytopenia, sorafenib administration was initiated at a dose of 400 mg daily. Although he received sorafenib for only 21 days, the patient exhibited complete regression of the tumors. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In considering the mechanism of liver failure in our patients, we found characteristics in common with previously reported patients with HCC who achieved CR on sorafenib monotherapy (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Of 15 patients, seven had portal vein tumor thrombi, two had portal thrombosis, three had tumor invasion into the inferior vena cava (IVC), two had portal LN swelling, and one had vascular-invading HCC ( Table 1).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In considering the mechanism of liver failure in our patients, we found characteristics in common with previously reported patients with HCC who achieved CR on sorafenib monotherapy (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Of 15 patients, seven had portal vein tumor thrombi, two had portal thrombosis, three had tumor invasion into the inferior vena cava (IVC), two had portal LN swelling, and one had vascular-invading HCC ( Table 1).…”
Section: Discussionsupporting
confidence: 66%
“…One had portal vein tumor thrombus (PVTT) and the other developed portal vein thrombosis (PVT) during the treatment. Although both PVTT and PVT are regarded as negative prognostic factors for patients with HCC, previous studies have identified several patients with deteriorated portal flow who achieved complete remission (CR) while being treated with sorafenib (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). We hypothesized that the pathogenesis of disease may be similar in HCC patients who achieve CR and those who experience liver failure while on sorafenib.…”
Section: Introductionmentioning
confidence: 98%
“…In the literature, three cases of severe cardiovascular complications in patients with a sorafenib monotherapy CR have been reported. With the exception of a case of renal cell carcinoma reported by Pantaleo et al (35), shown in Table II, Hagihara et al (36) and Shiozawa et al (37) reported CR of HCC treated with sorafenib following the failure of pretreatments (surgery, trans-arterial chemioembolization and percutaneous ethanol injection) and complicated by acute myocardial and cerebellar infarction, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Complete response to sorafenib has been reported previously in 40 case reports of patients with advanced HCC . Complete response to sorafenib in patients with bone metastasis is rare.…”
Section: Introductionmentioning
confidence: 85%
“…1,2 Complete response to sorafenib has been reported previously in 40 case reports of patients with advanced HCC. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Complete response to sorafenib in patients with bone metastasis is rare. In this case report, we describe CR to short-term sorafenib treatment in a patient with HCC and bone, lymph node, and peritoneal metastases.…”
Section: Introductionmentioning
confidence: 99%